Assessment of morphological changes induced by flow and flood pulses in a gravel bed braided river: The Tagliamento River (Italy) - Bertoldi, W.; Zanoni, L.; Tubino, M. (Geomorphology (Amsterdam, Netherlands), 2010)
Large gravel-bed braided rivers show a highly dynamic evolution, where even moderate flow pulses can produce significant morphological adjustment. An estimation of network variations is needed by river authorities as well as by ecologists for better managing river ecosystems. However, few field investigations have been performed to measure the effect of unsteady discharges in braided rivers. In this paper we report on the morphological changes induced by six different floods in a 1-km-long reach of the Tagliamento River, Italy. Topographic surveys were performed after each significant flood, and an automatic digital camera continuously monitored the planimetric configuration. Repeated measurements of cross section profiles allowed the quantification of the transported sediments volume and, in particular, provided a basis to estimate the percentage of the floodplain subject to morphological evolution. Data analysis showed a good relationship between peak flow level, active width, and mean bed level changes. Similarly, lateral channel shifting is likely to increase for larger floods. Monitoring of a range of discharges up to bankfull conditions revealed a fundamental difference between flow pulses (events on the average occurring one or more times per year) and flood pulses (with a return period larger than two years). The morphological evolution in the former case is mainly limited to a few active branches and is locally driven by bank erosion at the bend apex. On the other hand, larger floods induce a complete reworking of the network configuration, where bifurcations and confluences play a crucial role. Single morphological units (like branches, nodes, bars) are no longer recognizable after this type of event. Braided rivers are therefore characterized by the occurrence of two different spatial and temporal scales that force the ecosystem dynamics.